PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA JASA KEPABEANAN DAN CUKAI (studi pada Kantor Pengawasan dan Pelayanan Bea dan Cukai Tipe Madya Cukai Kudus) - Ihsan Nur Handoyo, 0835020555; Muhaimin, Muhaimin (Students Journal of Economic and Management, 2014)
This study aims to identify and analyze the impact of service quality on perceived satisfaction of service users in KPPBC Tipe Madya Cukai Kudus. The study was conducted by taking a sample of the Customs and Excise service users that exist in the KPPBC Tipe Madya Cukai Kudus and use the questionnaire as a data collection tool. In scoring this assessment using a scale or measuring Linkert. The results showed that the quality of service that consists of Tangible (x1), Reliability (x2), Responsiveness (x3), Assurance (x4), and Empathy (x5) partially and jointly significant effect on service user satisfaction variable (y). The results of multiple linear regression analysis, equation Y = 0,197 x1 + 0,223 x2 + 0,183 x3 + 0,278 x4 + 0,216 x5. From these equations show that the most dominant variable Assurance compared with other variables to influence user satisfaction with the services of the regression coefficient of 0,278. The coefficient of determination (Adjusted R Square) of 0.771 which means that the variable Tangible, Reliability, Responsiveness, Assurance, and Empathy able to explain the service user satisfaction with the service at KPPBC Tipe Madya Cukai Kudus 77.1%, and the remaining 22.9% is influenced by other factors not examined Keywords : Quality of service, Tangible, Reliability, responsivenes, Assurance, and Empathy, service user satisfaction